The Stability of Growth Equilibrium: Comment - Sargent, J. R. (Quarterly Journal of Economics, 1962)
Journal Article The Stability of Growth Equilibrium: Comment Get access J. R. Saegent J. R. Saegent Worcester College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 3, August 1962, Pages 494–501, https://doi.org/10.2307/1879636 Published: 01 August 1962